Employee Perceptions About Participation in Decision-Making in the COVID Era and Its Impact on the Psychological Outcomes: A Case Study of a Cooperative in MONDRAGON (Basque Country, Spain) - Arregi, Aitziber; Gago, Monica; Legarra, Maite (Frontiers in Psychology, 2022)
This research aims to study possible effects or impacts of COVID-19 in the context of a democratic organizational system analyzing how COVID-19 has influenced employees’ perception of their participation in decision-making and its impact on some psychological outcomes and emotions. COVID-19 has accelerated the process of implementation of new frameworks at work (digitalization, teleworking, new skills and abilities) that have generated the modification of culture and employee management practices. Our hypothesis are, on the one hand, that COVID-19 has generated changes in participation structures and internal communication mechanisms, having to make modifications not to deteriorate the perception of employees about their participation in decision making. On the other hand, COVID-19 has generated changes in the psychological outcomes and emotions of the employees. In the study, we analyze a cooperative belonging to the MONDRAGON cooperative group, where participation in decision-making and ownership is in its DNA. Through qualitative (5 focus groups) and quantitative (short questionnaire) methodologies, involving 42 employees, we investigate firstly, how COVID-19 has affected perceptions about participation in decision-making analyzing what role has played internal communication in these perceptions. Secondly, we investigate how COVID-19 has affected psychological outcomes and emotions. In this case, the perceptions arising from participation in decision-making focus on the assessment that participators make of the governance channels and the day-to-day meetings. Therefore, their appropriateness seems to be a key factor in the perception of participation in the COVID-19 era. Differences have been detected between the perceptions of blue and white collar employees. Such differences have also been founded in the psychological outcomes and emotions. Although this is a single case study, the analysis carried out provides elements of reflection to modify and restructure the decision-making and participation mechanisms, adapting them to the needs of blue and white collar employees in order to "guarantee" the expected outcomes.